PRACTICAL STRATEGIES FOR TEACHING ENGLISH TO YOUNG LEARNERS - Zainollah, Zainollah (Universitas Islam Madura, 2016)
Teaching English to young learner is very different from teaching English to adolescent and adults. There are three learner groups in English language teaching (ELT). There are young children, adolescent and adult. The three learner groups have crucial differences in terms of language learning needs, language competence emphasized, and cognitive skill addressed. Understanding the ideas and strategies for teaching English to young learners is very urgently needed for English teachers to design and develop learning activities for children. This article tries to explain some practical strategies or ideas in teaching English to young learners (TEYL). The practical strategies that can be practiced in the teaching English to young learners are: teaching with pictures, visual and realia, teaching with movement and games, teaching with stories and teaching with music or song. Hopefully, these strategies can help teachers especially teachers of young learners in designing and developing learning activities in the classroom.